Perceptions of Teachers Toward Nature of Science (NOS) and Attitude toward Teaching Nature of Science (NOS) - Kaur, Nitu; Lalhmingliani, Margaret; Vadhera, R.P. (Voices of Teachers and Teacher Educators, 2020)
The present research aimed to study the perceptions of teachers towards the Nature of Science (NOS) and their attitude towards teaching about the Nature of Science (NOS). In the study all the participant teachers exclusively belonged to the different science disciplines of higher education level i.e. college and university teachers of Mizoram University, Aizawl, Mizoram for the academic year 2019. Sample comprised of randomly selected 50 teachers out of a total 145 population of science teachers. The perceptions of participants towards NOS and their attitude towards teaching NOS were measured through VOSE (Views on Science and Education) questionnaire. On an average teachers held good perception toward NOS and a positive attitude toward teaching about NOS to their students. It was also found that the teachers’ perception on NOS differed significantly about their discipline of practice. This result was supported using Student ‘t’ test and one- way ANOVA analysis. However, teachers’ perception on NOS did not differ significantly with regard to their teaching experience and gender. Similarly, teachers’ attitude toward teaching NOS did not differ significantly with regard to their discipline of practice, teaching experience and gender